Sub-millennial eruptive recurrence in the silicic Mangaone Subgroup tephra sequence, New Zealand, from Bayesian modelling of zircon double-dating and radiocarbon ages - Danišik, Martin; Lowe, David J.; Schmitt, Axel Karl; Friedrichs, Bjarne; Hogg, Alan G.; Evans, Noreen J. (Quaternary science reviews, 2020)
Accurate dating of young (<1 Ma) volcanic eruptions has long been a challenge for modern geochronology given the scarcity of datable mineral phases and low quantities of radiogenic daughter products. Combined U-Th-Pb and (U-Th)/He dating of zircon (i.e., zircon double-dating, ZDD) is a relatively new dating approach that offers a viable option for dating zircon-bearing volcanic and pyroclastic deposits as young as ca. 3 ka, and has a great potential for application in many fields within the Quaternary sciences, including volcanology, palaeoclimatology, and archaeology. In our study, a stratigraphically and spatially well-defined sequence of 13 rhyodacitic to rhyolitic tephra beds - the Mangaone Subgroup (MSg) - erupted from the Okataina Volcanic Centre (OVC), is used as a natural laboratory to conduct a cross-validation experiment in which the ZDD eruption ages are compared with published and new radiocarbon (14C) eruption ages. These ZDD and 14C ages are then used together to underpin a Bayesian age model developed (using ChronoModel) to provide new ages for the entire MSg sequence. New ZDD eruption ages of 36.1 ± 4.4, 31.5 ± 5.2, 30.9 ± 5.6, 31.2 ± 4.4 ka BP for four MSg tephras (Units D, I, J, and K, respectively) are statistically indistinguishable from 14C-based eruption ages. These results validate the feasibility of ZDD to date late Quaternary eruptions accurately. The Bayesian age sequence model provides provides an eruptive geochronology eruptive geochronology for all 13 MSg tephra beds for the first time (and for the stratigraphically-interbedded Taupo-volcano-derived Tahuna tephra, 38.4−1.4+1.7 ka BP), and constrains the beginning of the MSg eruption period to 42.7−3.5+3.7 ka BP (Unit A) and the end to 30.6−1.5+0.6 ka BP (Unit L). Thus, the entire MSg sequence was emplaced in ∼12,100 years, representing an eruption frequency of one event per ∼930 years on average. Our study demonstrates the efficacy of ZDD to yield accurate eruption ages on pyroclastic deposits, highlighting its potential for dating young (<1 Ma) magmatic and eruption events that are difficult to date by other geochronological methods, and also shows that ZDD dates can be integrated with 14C ages using Bayesian modelling to develop new age models for long sequences of tephra beds, in this case those of the MSg tephras that were deposited during MIS 3. In addition, the U-Th zircon crystallization data revealed distinct U-Th model age spectra for older and younger MSg tephras, providing geochronological evidence for a decreasing degree of interconnectedness within the OVC magma reservoir during the MSg eruption period that followed caldera collapse associated with the pre-MSg Rotoiti (Rotoehu) eruption at ca. 45 ka BP.
Gesehen am 25.11.2020